CircAnks1a in the spinal cord regulates hypersensitivity in a rodent model of neuropathic pain - Su-Bo Zhang (Nature Portfolio, 2019)
Circular RNAs are non-coding RNAs that are enriched in the CNS, but their role in chronic pain is not known. Here the authors show that CircAnks1a in dorsal horn neurons contributes to pain-like hypersensitivity in a rodent model of neuropathic pain, via a VEGF mechanism.